Polymicrobial Necrotizing Fasciitis in a Dog: The Involvement of Macrococcus caseolyticus, Proteus mirabilis, and Escherichia coli - Acheampong, O.D.; Enyetornye, B.; Osei, D. (Hindawi, 2021)
A male mixed breed dog was presented with two large wounds, extending the epidermis, dermis, and fascia: one at the dorsum of the thoracolumbar region and the other at the lumbosacral area. Lesions had extended inconspicuously to the dorsum of thorax affecting a large area, which showed regions with necrotic and crepitating foci after shaving. Based on histopathological and bacterial culture examinations, polymicrobial necrotizing fasciitis (NF) was diagnosed. Using the Bruker MALDI Biotyper identification technique, Macrococcus caseolyticus, Proteus mirabilis, and Escherichia coli were identified. Hitherto, there is no report on these bacteria linking them simultaneously to NF in a dog. In addition, the authors highlight other microbes associated with NF in humans and animals.
Research Article